Is an antireflux procedure necessary for a successful appendicostomy? The simplified Malone antegrade continence enema procedure - S J Karmarkar; Achugatla Sushma; A P Bangar; J Krishnan (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of this study was to present the long-term institutional experience and outcomes of our Malone antegrade continence enema (MACE) procedure using the proximal appendix without any antireflux procedure. Materials and Methods: A single-center prospective study of 29 children undergoing a simplified Malone antegrade continence enema (SMACE) procedure from 2006 to 2017 was conducted using the appendix, whole or split. The mean follow-up period was 11.5 years (ranging from 5 to 16 years). Results: In 25 children, the proximal appendix was used, and in 4 cases, the whole appendix was used as a conduit. On follow-up, the MACE channel has been working well in 29/29 patients. Among the complications, seven patients had stomal stenosis, which was managed by home dilatation. There was no reflux of stools seen in any of the patients. Conclusion: The SMACE procedure, without incorporating an antireflux mechanism, is technically simpler and saves operative time. Most importantly, the results are satisfactory and comparable with procedures using antireflux techniques.